2023
DOI: 10.1111/jbg.12776
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genomic breeding values and their accuracies for carcass traits in Jeju Black cattle using whole‐genome SNP chip panels

Abstract: The objective of the present study was to evaluate the breeding value and accuracy of genomic estimated breeding values (GEBVs) of carcass traits in Jeju Black cattle (JBC) using Hanwoo steers and JBC as a reference population using the single‐trait animal model. Our research included genotype and phenotype information on 19,154 Hanwoo steers with 1097 JBC acting as the reference population. Likewise, the test population consisted of 418 genotyped JBC individuals with no phenotypic records for those carcass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…Our study reported h 2 (GBLUP, Bayes B) for the Hanwoo population as follows: CWT (0.42, 0.47), EMA (0.36, 0.37), BF (0.36, 0.36), and MS (0.47, 0.42). These estimates significantly differ from the h 2 estimates obtained in recent studies by Haque et al [29], who reported h 2 for CWT, EMA, BF, and MS using the GBLUP method as 0.30, 0.26, 0.26, and 0.34, respectively. Mehrban et al [30] also estimated h 2 for these four traits using Bayes C and Bayes L methods and obtained almost similar values.…”
Section: Estimation Of Variance Components and Heritabilitycontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study reported h 2 (GBLUP, Bayes B) for the Hanwoo population as follows: CWT (0.42, 0.47), EMA (0.36, 0.37), BF (0.36, 0.36), and MS (0.47, 0.42). These estimates significantly differ from the h 2 estimates obtained in recent studies by Haque et al [29], who reported h 2 for CWT, EMA, BF, and MS using the GBLUP method as 0.30, 0.26, 0.26, and 0.34, respectively. Mehrban et al [30] also estimated h 2 for these four traits using Bayes C and Bayes L methods and obtained almost similar values.…”
Section: Estimation Of Variance Components and Heritabilitycontrasting
confidence: 99%
“…Additionally, the backfat thickness was estimated to be 14.09 (14.53 for steers), and the eye muscle area was 94.16 (96.70 for steers) in our study, both of which showed higher estimates compared to the values reported by Kwon. In another recent report by Haque et al [29], the authors examined genomic selection methods for the same four carcass traits in Jeju Black cattle, using Hanwoo steers as a reference population at approximately 24 to 35 months of age. The recorded average values for CWT, EMA, BF, and MS were 445.00 kg, 96.70 cm 2 , 14.20 mm, and 5.99, respectively, which aligns closely with our steers data records.…”
Section: Summary Statistics Of the Phenotypesmentioning
confidence: 99%
“…Notably, the genomic BLUP models and Bayesian variable selection or variable shrinkage models have gained widespread recognition and utilization. The idea of enhancing body conformation traits of Korean Holsteins by GS led to the estimation of GEBVs and their accuracy using GBLUP model, which presupposes a homogenous variance across SNPs and an equal contribution from each SNP to the overall variance [ 37 ]. Approximately a decade ago, Misztal et al [ 38 ] introduced a novel approach known as the single-step genomic BLUP method (ssGBLUP).…”
Section: Resultsmentioning
confidence: 99%
“…The widespread application of GBLUP within livestock species is primarily due to the polygenic nature observed in most traits [ 39 ]. Additionally, the GBLUP method is favored for its simplicity, lower computational requirements, and higher accuracy in contrast to the conventional pedigree-based BLUP (PBLUP) approach [ 37 ]. Other species have transitioned away from GBLUP to single-step methods, especially in dairy cattle, largely due to the cost and technical complexities associated with the latter.…”
Section: Resultsmentioning
confidence: 99%
“…Hanwoo beef is known worldwide as a highly-marbled, tender and palatable meat type ( Cho et al, 2017 ; Chung et al, 2018 ). In contrast to the Hanwoo, the other three remaining breeds are only reared in several locals with a limited population size (hundreds to thousands of heads per breed; Alam et al, 2021 ; Haque et al, 2023 ; Park et al., 2020 ). Recently, beef producers have paid more attention to these cattle breeds ( Song et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%